Howard S. Liebengood papers - Liebengood, Howard S. (Howard Scholey), 1942-; Baker, Howard H. (Howard Henry), 1925-
Correspondence, memoranda, minutes, speeches, reports, legislative proposals, research files, notebooks, travel materials, campaign materials, financial and legal papers, Senate floor statements, newspaper clippings, photographs, and other papers pertaining primarily to Liebengood's service on the minority staff of the U.S. Senate Select Committee on Presidential Campaign Activities (known as the Watergate Committee), as minority staff director of the U.S. Senate Select Committee on Intelligence, and as legislative counsel to Senate minority leader Howard H. Baker. Topics include the role of the Central Intelligence Agency (CIA) in Watergate and other aspects of the affair, scope of CIA and Federal Bureau of Investigation (FBI) operations, renewed investigation of John F. Kennedy's assassination, Panama Canal treaties (1977), Koreagate scandal (1977-1978), Strategic Arms Limitation Talks II, Abscam Bribery Scandal (1980), Billy Carter's activities relating to Libya, and other issues during Jimmy Carter's administration. Includes a portion of Baker's papers (1975-1982).
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Lawyer and U.S. Senate sergeant at arms.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baker, Howard H. -- 1925-; Carter, Billy; Carter, Jimmy, -- 1924-; Kennedy, John F. -- 1917-1963 -- Assassination; Nixon, Richard M. -- 1913-1994.; Panama Canal Treaties -- (1977); United States. -- Central Intelligence Agency; United States. -- Congress. -- Senate. -- Select Committee on Intelligence; United States. -- Congress. -- Senate. -- Select Committee on Presidential Campaign Activities; United States. -- Federal Bureau of Investigation; Abscam Bribery Scandal, 1980.; Arms control; Intelligence service -- United States; Political corruption -- United States; Watergate Affair, 1972-1974.; Watergate Trial, Washington, D.C., 1973.; Korea -- Foreign relations -- United States; Libya -- Foreign relations -- United States; Panama -- Foreign relations -- United States; Panama Canal (Panama) -- History; Soviet Union -- Foreign relations -- United States; United States -- Foreign relations -- Korea; United States -- Foreign relations -- Libya; United States -- Foreign relations -- Panama; United States -- Foreign relations -- Soviet Union; United States -- Politics and government -- 1969-1974.; United States -- Politics and government -- 1974-1977.; United States -- Politics and government -- 1977-1981.; Lawyers; Sergeants at arms, U.S. Senate